Δ24-Sterol Methyltransferase Plays an Important Role in the Growth and Development of Sporothrix schenckii and Sporothrix brasiliensis - Borba-Santos, Luana P.; Visbal, Gonzalo; Gagini, Thalita; Rodrigues, Anderson M.; de Camargo, Zoilo P.; Lopes-Bezerra, Leila M.; Ishida, Kelly; de Souza, Wanderley; Rozental, Sonia (Frontiers in Microbiology, 2016)
Inhibition of ∆24-sterol methyltransferase (24-SMT) in Sporothrix schenckii sensu stricto and Sporothrix brasiliensis was investigated in vitro. The effects on fungal growth and sterol composition of the 24-SMT inhibitor 22-hydrazone-imidazolin-2-yl-chol-5-ene-3-ol (H3) were compared to those of itraconazole. MIC and MFC analysis showed that H3 was more effective than itraconazole against both species in both their filamentous and yeast forms. H3 showed fungistatic activity in a time-kill assay, with inhibitory activity stronger than that of itraconazole. GC analysis of cell sterol composition showed that sterols present in control cells (ergosterol and precursors) were completely replaced by 14-methylated sterols after H3 exposure. Itraconazole only partially inhibited ergosterol synthesis but completely arrested synthesis of other sterols found in control cells, promoting accumulation of nine 14-methyl sterols. Based on these results, we propose a schematic model of sterol biosynthesis pathways in S. schenckii and S. brasiliensis. Effects on cell morphology due to 24-SMT inhibition by H3 as analyzed by SEM and TEM included irregular cell shape, reduced cytoplasmic electron-density, and reduced thickness of the microfibrillar cell wall layer. Moreover, 24-SMT inhibition by H3 promoted mitochondrial disturbance, as demonstrated by alterations in MitoTracker® Red CMXRos fluorescence intensity evaluated by flow cytometry. When used in conjunction with itraconazole, H3 enhanced the effectiveness of itraconazole against all tested strains, reducing at least half (or more) the MIC values of itraconazole. In addition, cytotoxicity assays revealed that H3 was more selective towards these fungi than was itraconazole. Thus, 24-SMT inhibition by H3 was an effective antifungal strategy against S. schenckii and S. brasiliensis. Inhibition of the methylation reaction catalyzed by 24-SMT has a strong antiproliferative effect via disruption of ergosterol homeostasis, suggesting that this enzyme is a promising target for novel antifungal therapies against sporotrichosis, either as sole treatments or in combination with itraconazole.